Understanding the Factors Influencing Customer Intention to Subscribe to Spotify Premium in Indonesia - Zhafarina Zatalini; Nafit de Amalia; Tri Wismiarsi (Program Studi Magister Manajemen FE Unsri, 2023)
ABSTRACTResearch Aim – This research aims to investigate the factors of attitude and perceived behavior control of young-adult customers in Indonesia that influence their intention to subscribe to Spotify premium.Design/Methodology/Approach – This study is a quantitative study using descriptive and regression analysis. Data were collected from 100 respondents who have been subscribing to Spotify Premium services for at least 1 week.Research Result – The results reveal that attitude and perceived behavioral control significantly influence the intention to subscribe, with attitude having a greater influence on customers’ intention to subscribe.Research limitations – The age range of participants in the current study is restricted to those between the ages of 17 and 30. The generalizability of the study is also constrained because there were only 100 samples collected altogether.Originality/value – This study is conducted in Indonesia while the previous research was conducted in China. The present research help provides feedback for the streaming music services industries, especially in Indonesia to improve their marketing strategies’ performance based on customer behavior and psychology to increase sales of businesses.Keywords: Spotify Premium, Music Streaming Service, Attitude, Perceived Behavioral Control, Intention to Subscribe.